Temporary and permanent technology lock-ins in the quality-differentiated Bertrand competition - Anton Bondarev; Frank C. Krysiak (University of Basel, Center of Business and Economics (WWZ), 2017)
We consider a setting where strategic behavior of r&d firms can lead to different types of a technology lock-in, permanent or temporary, in an eventually inferior technology. The simple setting with one incumbent and one potential entrant may lead to a wide variety of possible strategic regimes. We study conditions on relative market strength of the incumbent and the entrant which lead to different strategic actions and demonstrate, that such a strategic behavior is not always socially suboptimal, since it may lead to faster development of the existing technology due to persistent threat of the potential entrant. We further elaborate on the selection of support tools which may induce the development of new technology in the second-best world and establish criteria for these tools to be social welfare improving ones.
Keywords: C61; O31; O38; 330; technology lock-in; technological change; strategic interaction; r&d policy; multiple regimes